ASNTR's Venture into a Hybrid Conference: Lessons Learned During the COVID-19 Pandemic. (20th October 2021) - Sanberg, Paul; Morrison, Donna C; Bjugstad, Kimberly
The 28th American Society for Neural Therapy and Repair (ASNTR) returned to the Sheraton Sand Key in Clearwater Beach, Florida after an 18 month hiatus. Like nearly all conferences during the pandemic, the ASNTR conference was held in person while offering a virtual option to the event. These formats are advantageous for those under travel restrictions or personal constraints, but they lack the spontaneity of in-person connections. Highlights from the meeting included the return of the Bernard Sanberg Memorial Award and the Roy Bakay Memorial lecture. The presidential lecture was given by Gabriel de Erausquin, who discussed the possibility of long-term CNS effects resulting from SARS-CoV2 infection. With both virtual and in-person events, including oral and poster presentations, the ASNTR managed to maintain the unique essence of this small important meeting.